Assessing the Influence of Water Conservancy Projects on China’s Reserve Resources for Cultivated Land - Yuan Yao; Guohua He; Wei Li; Yong Zhao; Haihong Li; Fan He (Land, 2023)
The development of reserve resources of cultivated land (RRCL) is a vital way of supplementing cultivated land in the northern arid and semi-arid regions of China. This study developed a suitability evaluation system for reserve resources of cultivated land from the nature–function–environment perspective. The evaluation considered the construction of water conservancy projects, establishing two scenarios of rain-fed and irrigated agriculture. The evaluation results for unused land were divided into four levels, including highly suitable, relatively suitable, moderately suitable and unsuitable, using the three-dimensional Rubik’s cube spatial classification method. The results show that: (1) Under the rain-fed agriculture scenario, the developable quantity and quality of unused land were poor. The potential area of reserve resources of cultivated land only accounted for 5% of the total area. (2) Under the irrigated agriculture scenario, the potential area of reserve resources of cultivated land increased to 21% of the total unused land. The areas were mainly distributed in Xinjiang, Inner Mongolia, and Gansu. The research considered the impact of water conservancy projects on the development and utilization of reserve resources of cultivated land. It can provide references for the development of arable land resources and territorial spatial planning in China.